2008
DOI: 10.1007/s00417-008-0897-1
|View full text |Cite
|
Sign up to set email alerts
|

Triamcinolone acetonide for refractory pseudophakic cystoid macular edema after intravitreal bevacizumab

Abstract: Dear Editor, An important cause of unfavourable visual outcome after cataract surgery is pseudophakic cystoid macular edema (PCME). The pathophysiology of PCME has not been clearly elucidated; however, a breakdown of the bloodretinal barrier secondary to postoperative inflammation is thought to be one of the main factors involved. In the absence of vitreomacular traction, a wide range of therapeutic options including topical non-steroidal anti-inflammatories, acetazolamide, topical steroids, periocular steroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…66 A different published case study, however, showed failure of edema to resolve after 3 injections of bevacizumab followed by improvement with a sub-Tenon injection of triamcinolone. 67 In another retrospective series, 10 eyes of 10 patients with refractory CME after cataract surgery were injected with intravitreal bevacizumab (1 or more times). 68 The bestcorrected visual acuity improved from a mean of 20/80 to 20/32, associated with a significant decrease in mean central macular thickness, with 6 months of follow-up.…”
Section: Targeting Vascular Endothelial Growth Factormentioning
confidence: 99%
“…66 A different published case study, however, showed failure of edema to resolve after 3 injections of bevacizumab followed by improvement with a sub-Tenon injection of triamcinolone. 67 In another retrospective series, 10 eyes of 10 patients with refractory CME after cataract surgery were injected with intravitreal bevacizumab (1 or more times). 68 The bestcorrected visual acuity improved from a mean of 20/80 to 20/32, associated with a significant decrease in mean central macular thickness, with 6 months of follow-up.…”
Section: Targeting Vascular Endothelial Growth Factormentioning
confidence: 99%
“…Most postoperative CME cases can be successfully treated either with topical and systemic nonsteroidal antiinflammatory drugs or periocular, systemic, and intravitreal corticosteroid such as a dexamethasone intravitreal implant (OZURDEX®) or intravitreal anti-VEGF therapy. 3,[15][16][17][18][19][20][21][22][23] However, a particular subset of patients develops recalcitrant CME which could benefit from longer lasting intravitreal corticosteroids in order to achieve prolonged anatomical and functional improvement.…”
Section: Introductionmentioning
confidence: 99%